Política pública educacional como estratégia de programa de governo: o sistema Universidade Aberta do Brasil (UAB) - Oliveira, Luciana Charão de (2019)
This research deals with educational public policies, having as object of study: the Sistema Universidade Aberta do Brasil – UAB (Open University System of Brazil), considered as a public educational policy of great importance for Educação a Distância – EaD (Distance Education). The UAB System was implemented in the Lula Government (2003-2010), although there have been attempts in previous decades to establish an open university in the country. The main goal of this thesis was to present a analyse about the System UAB, understood as public educational policy whose configuration resembles a strategy of a government program. This public policy is based on some axes of operation and the axis explored on this thesis refers to the expansion of vacancies in the Brazilian Higher Education. From this objective, it is defended the thesis that the UAB System, sometimes called public policy, sometimes called the program, is presented as a public policy whose contradiction is explicit because it is a government program of the Lula Government whose central purpose was the expansion of public policies of a social nature, in this case, in the educational field. While the articulating axis of the UAB System has a social question - the expansion of vacancies in Higher Education to meet a repressed demand, on the other hand, the mechanisms used for the objective to be put into practice correspond to the proper mechanisms of a neoliberal policy . This corroborates for the fact that the education offered to be precarious.In this study, a historical-critical analysis was conducted based on a documentary and bibliographical research that sought into the historical context the movement and the contradictions through which the UAB System is configured, transformed and composed. The results of the survey showed that the expansion of vacancies in Higher Education occurred more intensely until the year 2014 and, according to the sources consulted, in 2013 the UAB System began to show signs of exhaustion due to the cuts in resources of the federal government. In 2018, the President of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – CAPES (Coordination of Improvement of Higher Education Personnel), in a letter to the Ministry of Education, communicated that, due to the cut in expenses for Education, in the year 2019 there may be a disruption of the UAB System. In short, the thesis that the fragility of the UAB System, sometimes a public policy, other times as a program of the government, is revealed by the impossibility of sustaining its own operation. The UAB system does not have its own physical institutional space and uses the infrastructure of the already consolidated universities, which end up worsening the conditions of public universities that are already precarious, conditions that especially concern are the infrastructure and human resources. Key words: Open University System of Brazil. Public educational policy. Distance education. Government program. Precarious education.